(untitled) (Our Nature, 2025)
This study documents new inclusions to the ichthyofauna of Nepal, focusing on four fish species: Cirrhinus cirrhosus, Labeo boggut, Piaractus brachypomus, and Oreochromis aureus. Ichthyological surveys were conducted in the Kankai River from August 2023 to July 2024, utilizing a combination of cast nets, gill nets, and local fishing tools. Specimens were subjected to detailed morphometric and meristic analyses, and their conservation statuses were reviewed. The findings underscore the importance of ongoing field investigations and conservation efforts to protect Nepal’s aquatic biodiversity, particularly in the face of increasing non-native fish species introductions.